The effectiveness of online social network-based intervention for stress management among SASMEC’s nursing staff - Mohd Rosaimi, Muhammad Izzuddin; Mat Zin, Nora; Zakaria, Rozanizam; Mohd Arifin, Siti Roshaidai (Universiti Kebangsaan Malaysia, 2023)
Introduction: There is an increasing body of research indicating that nurses are encountering substantial workplace stress, which has emerged as a global concern. In the past decade, there has been significant attention dedicated to the utilisation of online social network-based therapies for stress management among health care personnel. Nevertheless, there is a dearth of data about the efficacy of such interventions, particularly in the context of Malaysia. This study aims to investigate the effectiveness of an online social network-based intervention among nurses towards their level of stress, burnout and job satisfaction pre and post-intervention. Materials and Methods: This was an experimental study, without control, investigating pre and post online social network-based intervention effectiveness in reducing nurses stress and burnout, and improving their job satisfaction. A total of forty nurses participated in the intervention, which spanned a duration of eight weeks. The stress levels of nurses were evaluated with the Perceived Stress Scale (PSS-10), whilst the assessment of burnout levels was conducted utilising the Oldenburg Burnout Inventory (OLBI). The measurement of job satisfaction among nurses was conducted utilising the abbreviated version of the Minnesota Satisfaction Questionnaire (MSQ). Results: Following the intervention, there was a notable decrease in the level of stress (p-value: <0.01), burnout (p-value: <0.01), and work satisfaction (p-value: <0.01), all of which were statistically significant. Conclusion: In summary, the use of online social network-based interventions for stress management shows considerable potential in mitigating stress and burnout among nurses, while simultaneously enhancing job satisfaction.